Secured Recruitment Management System with Data Retention Approach - Mashitah Mohd Tobroni,; A Hamid, Isredza Rahmi (Applied Information Technology And Computer Science, 2023)
TAMCO Switchgear Sdn. Bhd. is an established electrical company specializing in the production of medium voltage switchgear. The company employs two primary methods for recruiting new employees which are manual system and a third-party seeking job portal. However, these methods present several challenges. The manual system is burdensome as applicants must email their applications to the Human Resource (HR) department, while the third-party portal poses data security risks. To address these issues, we proposed the development of a secured recruitment management system with data retention capabilities. This system aims to serve as an employment management platform for the HR department. By incorporating automated filtering mechanisms based on position requirements, the HR department can efficiently manage job applications and identify potential candidates. Furthermore, personal data stored in the database will be deleted after six months to comply with data retention guidelines. The project will follow an iterative waterfall development model and implement password hashing, salting, and Two-Factor Authentication (2FA) through One Time Passcodes (OTP) sent via email. This project is crucial for providing a reliable and secure job recruitment platform, reducing the risk of data breaches, and enhancing TAMCO Switchgear's credibility by prioritizing data protection and building trust with potential candidates.